Analysis on the impact of marketing costs on vegetable farmers in southern Mindanao - Jarabelo, Crystalle Lauren M.
This study aimed to determine the proportion of impact borne by each producing farmers in Southern Mindanao in the advent of increasing marketing costs. The proponent identified key informants through the employment of simple random sampling. A surveyed questionnaire was distributed among the 219 farmers containing inquiries concerning their marketing and production activities in the year 2001. The data gathered were summarised, tabulated and analyzed using the multiple regression. However, the proponent designed two data sets namely the aggregated and disaggregated, which has undergone a tedious combination of variables in order to come up a sound econometric models. Secondary data sources gathered from the different government and non-government offices were employed to potentially show in a much wider scale the market attributes, constraints and problems that were faced by the farmers as they engage into vegetable marketing. Data obtained was rigorously treated with multiple regression which was used in the estimation of both the supply and demand elasticities needed for the final calculation of the Margin-Fisher Model. The estimation results that were drawn in this study were carefully analyzed as this could be a potential venue that government policies be addressed in favor of the farmers.